Transcatheter Closure for Ventricular Septal Defect (VSD): Unveiling Key Predictors in Pediatric Interventions - Ria, Natal; Gunawijaya, Eka; Yantie, Ni Putu Veny Kartika (Jurnal Kardiologi Indonesia, 2023)
Background: Transcatheter closure of specific types of VSD has been widely performed, especially in developing countries, with encouraging follow-up results. Nevertheless, adverse outcomes and failure of closure may occur, which requires sufficient attention. Although transcatheter closure is still the preferable and safest procedure, the risk of failure can lead to the surgical VSD closure procedure. Methods: A retrospective cohort study was done in patients who underwent transcatheter VSD closure in the presence of AVP with or without AR at Integrated Cardiac Service Prof. Dr. I G N G Ngoerah General Hospital between July 2009 to June 2022. Failure to close was defined as a device failing to be implanted. Patient demographic and clinical data were collected. Results: Thirty-eight subjects were enrolled, 10 failed to close, where 8 out of 10 of the failure group were with aortic regurgitation, and 7 of the said group were SADC type. There were 16 males and 22 females. Among 38 subjects, 23 have perimembranous outlet VSD, and 15 have subarterial doubly committed VSD. Aortic regurgitation was found in 25 of 38 subjects. Transcatheter closure was done either by a retrograde technique using the Amplatzer Duct Occluder-II or an antegrade technique using the NIT occlude and MFO in 11, 3, and 24 subjects, respectively. The failure happened in 10 patients, 3 of them had minor complications, and 7 had no complications. There are 2 patients out of 10 with membranous septal aneurysms that failed to close. The final analysis identified VSD type SADC (RR 3.578; 95%CI 1.093 to 11.711; p = 0.030) as an independent factor associated with predictors of transcatheter closure failure in pediatric patients with VSD. Conclusion: Failure to close in transcatheter closure is higher in the SADC type compared to the PMO type. Transcatheter closure appears to be feasible but still challenging in our center.Thsi article has a related Erratum.